Respostas

2014-03-22T10:46:53-03:00
Uma P.A. de 3 termos é igual a x – r, x, e x + r.
Dessa forma, (x - r) + (x) + (x + r) = 15
                     3x - r + r = 15
                     3x = 15
                     x = 5



(x - r) . x . (x + r) = 80
(5 - r) . 5 . (5 + r) = 80
(5 - r) . (5 + r). 5 = 80
(25 - r²) . 5 = 80
125 - 5 .r² = 80
-5r² = -45   .(-1)
5r² = 45
r² = 9
r = 3; r = -3


Para r = 9 --> P.A = (x - r), x, (x + r)
                     P.A = (5 - 9), 5, (5+9)
                     P.A = (-4,  5,  9)

Para r = -3
        P.A = (x - r)     (x)  (x + r) 
        P.A = (5 - (-3)), 5, (5 + (-3))
        P.A = (8,  5,  2)